Workshop Calistung berbasis Pictures Themes bagi Anak Usia Dini - Rajab Ansari; Heni Mulyani Pohan; Elisa Elisa; Mutiara Lubis; Ayunda Sabrina Sormin; Jessica Linda Mora; Hafni Junita Harahap (Asosiasi Lembaga Pendidikan Tenaga Kependidikan Perguruan Tinggi Muhammadiyah Aisyiyah(ALPTK PTMA), 2022)
“CALISTUNG”refers to the achievement of children on reading, writing, and counting. “CALISTUNG” becomes one indicator for the children on their development in the first grade of elementary school. Commonly, the children on its will have much time in the home with their mother, in which, the mother needs to look the development of them in order they have well achievement on “CALISTUNG”. For this case, the achievement will be a benefit for the children to enrich as well as develop their knowledge for the future. Thus, an appropriate strategy from the mother should be needed to improve the achievement of thei children, whereas, it is one indicator. By having this program, the team tries to describe an appropriate strategy for the mother in developing as well as improving the achievement of “CALISTUNG” based on visual media, in which, it is focused to the mother’s community in University of Muhammadiyah Tapanuli Selatan. This program is taken based on workshop method, it gives the materials about developing and improving achievement of the children on “CALISTUNG” based on visual media. The result shows that there is an effective achievement of the audiences to maximal the using of visual media in improving the achievement of their children on “CALISTUNG”. Hence, they can have the maximal using of an appropriate visual media to manage the development of their children on “CALISTUNG, whereas, they gets the media based on children needs.